(untitled) (Latakia University Journal -Medical Sciences Series, 2016)
تهدف هذه الدراسة إلى تقييم كفاية الرد واستقرار التثبيت لكسور زاوية الفك السفلي باستخدام صفيحة صغيرة مفردة مطواعة غير ضاغطة موضوعة عبر مقاربتين (من داخل التجويف الفموي- وداخل فموي عبر الخد) . شملت الدراسة 20 مريضاً من المرضى المراجعين لمشفى الأسد الجامعي ومصابين بكسور أحادية أو ثنائية الجانب غير المتبدلة بشدة وغير المتفتتة في زاوية الفك السفلي وذلك في الفترة مابين ايلول 2011 وكانون الأول 2013. قسمت عينة البحث إلى مجموعتين واستخدمت مقاربتين جراحتين وطبقت الصفائح في أمكنة تثبيت متعارف عليها وفق مبادئ وبروتوكول Champy. جرى تقييم كفاية الرد واستقرار التثبيت من خلال الصور الشعاعية المأخوذة بعد العمل الجراحي مباشرة وتضمنت المراقبة السريرية كلا من الإطباق ، الفعالية المضغية, المضاعفات المتطورة بعد العمل الجراحي(الإنتان – انكشاف صفيحة التثبيت ) وذلك بعد شهر، ستة أشهر وسنة. أظهرت النتائج وجود فروق ذات دلالة إحصائية خلال فترة المتابعة بعد شهر وبعد ستة أشهر وذلك بالنسبة لجميع المتغيرات المدروسة وذلك لصالح المقاربة عبر الخد بينما لم تكن هناك فروق ذات دلالة بعد سنة من المتابعة. أظهرت الدراسة أن استخدام المقاربة داخل الفموية مع استخدام المدخل عبر الخد كانت الافضل من حيث عدم انكشاف الصفيحة وتطور الإنتان والأكثر سهولة مقارنة مع المدخل الفموي وذلك بالنسبة للمتغيرات المدروسة . The purpose of this study was to evaluate the reliability of a single malleable non- commpression titanium miniplate in fixation and stability of fractures of the mandibular angle using two approaches(.transbuccal and intra-oral approach, or intra-orally alone) . The research sample included 20 patients from patients who attended AL Assad University Hospital with Unilateral or bilateralun-comminuted mandibular angle fractures in the period between September 2011 and October 2013. The research sample was divided into two groups depending on the two approaches that have been used . Adequacy of the reduction and stability of fixation were evaluated through Radiographic examinations immediately after surgery. Postoperative assessment was based on clinical examination after 1 month, 6 monthes and a year to evaluate: Occlusion, Masticatory efficiency, Maximum mouth opening range, and Other complications(infection –mini-plate exposure). The results of the present study showed that there were statistical difference between the two approaches(transbuccal and intra-oral approach, or intra-orally alone) regarding Occlusion, Masticatory efficiency and Other complications after 1 and 6 months while there was no statistical difference between the approaches after 1 year . we Concluded that using the combined transbuccal/oral approach was the best regarding(infection and mini-plate exposure) and compared with intra-oral approach .